The U.S. Army and the New National Security Strategy - Davis, Lynn E. (RAND Corporation, 2003)
This book examines the Army's role in the war on terrorism; the Army's homeland security needs; the implications of increased emphasis on Asia; the Army's role in coalition operations; the unfinished business of jointness-the lessons learned from operations and how to prepare for the future; the Army's deployability, logistical, and personnel challenges; and whether the Army can afford its Transformation. These examinations are bracketed by an introduction, a description of the Army's place in the new national security strategy, and a summary of the authors' conclusions.